7-Aminoactinomycin D for apoptosis staining in flow cytometry - Zembruski, Nadine Cécile Luise; Stache, Vanessa; Haefeli, Walter E.; Weiß, Johanna (Analytical biochemistry, 2012)
7-Aminoactinomycin D (7-AAD) is a DNA dye that distinguishes viable, apoptotic, and late apoptotic/dead cells in flow cytometry. Several staining protocols using 7-AAD have been described, but data on the influence of the 7-AAD concentration on the readout are not available. Therefore, we compared the results obtained by staining with 1, 5, 10, and 20μg/ml 7-AAD for 20min with the PE-Annexin V Apoptosis Detection Kit and Cell Death Detection ELISAPLUS in lymphocytes and CEM human leukemia cells. The results showed that 7-AAD staining with 5, 10, and 20μg/ml, but not with 1μg/ml, is suitable for quantification of apoptosis in flow cytometry.